2011
DOI: 10.1590/s0102-86502011000800016
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic evaluation of the use of a latex prosthesis in videolaparoscopic inguinoplasty: an experimental study in dogs

Abstract: PURPOSE:To evaluate the morphological aspects of the behavior of 4 types of latex biomembranes implanted in preperitoneal videolaparoscopic inguinoplasty. METHODS: Sixteen inguinoplasties were performed in 12 dogs: group 1 received an impermeable latex biomembrane in the right inguinal region and a prolene prosthesis, as control, in the contralateral inguinal region; groups 2, 3 and 4 received latex biomembranes respectively containing impermeable polyamide, 1-mm thick porous polyamide and 0.5-mm thick porous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…The authors of the presented study did not identify any of the above-mentioned postoperative complications. The obtained results are comparable with those reported by other authors who experimentally used endoscopic surgery to close inguinal canals in dogs [15,21]. However, it should be taken into account that the groups of animals involved in the assessment of minimally invasive methods were small.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The authors of the presented study did not identify any of the above-mentioned postoperative complications. The obtained results are comparable with those reported by other authors who experimentally used endoscopic surgery to close inguinal canals in dogs [15,21]. However, it should be taken into account that the groups of animals involved in the assessment of minimally invasive methods were small.…”
Section: Discussionsupporting
confidence: 87%
“…Yet, the authors point out that laparoscopic repair of the inguinal hernia has not yet been reported in a series of dogs or cats [14]. Sousa et al [21] present an experimental study into the application of various prostheses in the laparoscopic treatment of inguinal hernia in dogs. Yet, the authors do not describe the endoscopic technique used in the surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Canine models may provide important information for vascular surgery research [18][19][20][21][22][23][24][25] . Kuzuya et al 22 investigated the healing process of ePTFE vascular access grafts (internal diameter: 5 mm, length: 15 cm) with various intermodal distances.…”
Section: Early Postoperative Changes In Hematological Erythrocyte Agmentioning
confidence: 99%
“…A natural biomembrane prepared with latex extracted from the rubber tree Hevea brasiliensis and polymerized with 0.1% polylysine was developed by the Department of Biochemistry of the Faculty of Medicine, of Ribeirao Preto, University of Sao Paulo. The membrane was used experimentally as a cicatrization-inducing material on the injured esophageal walls of dogs and was shown to lead to a marked increase in vascularization and epithelialization 3,4 . When similar material was used clinically it led to a significant increase in the granulation tissue of phlebopathic ulcers in the legs of patients and to a concomitant reduction of pain during treatment 5,6 .…”
Section: Introductionmentioning
confidence: 99%